Risk assessment using ICP-MS of heavy metals in groundwater in Upper Egypt - Bassioni, Ghada; Ashraf, Kirollos; Abd Elhameed, Amr (JNRD - Journal of Natural Resources and Development, 2015)
It is of great importance to assess the pollution of groundwater as it makes up about twenty percent of the world’s freshwater supply. Environmental laws in Egypt are correlated with protecting water resources from contamination and generally set the maximum limits for the concentration of different hazardous components in wastewater before it is discharged to sea water, rivers, groundwater and the public sewer system. Groundwater from Samalout, Al Minya governorate, Egypt, is studied by analysing its heavy metal content using Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Furthermore, the obtained heavy metal concentrations are compared with permissible limits set by environmental organizations such as the World Health Organization (WHO) and the United States Environmental Protection Agency (US-EPA). Comparing the heavy metal concentrations with the groundwater in question clearly demonstrated that the water in this resource should not be directly used for drinking and requires some degree of treatment before usage. For example, concentrations of chromium and lead are far above the maximum permissible limit. The consequent health risks due to the usage of contaminated water are identified in this study as well.
Keywords: Groundwater; Inductively coupled plasma-mass spectrometry; Permissible limits; Pollution